Enhancing biogas production from vinasse in sugarcane biorefineries: Effects of urea and trace elements supplementation on process performance and stability. (October 2016) - Janke, Leandro; Leite, Athaydes F.; Batista, Karla; Silva, Witan; Nikolausz, Marcell; Nelles, Michael; Stinner, Walter
Highlights: A new method to stabilize the anaerobic digestion of sugarcane vinasse is proposed. Urea addition increased alkalinity but not prevented the process failure. The addition of KH2 PO4 induced volatile fatty acids accumulation. Urea and trace elements addition improved the process stability in UASB reactor. A stable specific methane production of 239 mL g COD −1 was achieved. Abstract: In this study, the effects of nitrogen, phosphate and trace elements supplementation were investigated in a semi-continuously operated upflow anaerobic sludge blanket system to enhance process stability and biogas production from sugarcane vinasse. Phosphate in form of KH2 PO4 induced volatile fatty acids accumulation possibly due to potassium inhibition of the methanogenesis. Although nitrogen in form of urea increased the reactor's alkalinity, the process was overloaded with an organic loading rate of 6.1 g COD L −1  d −1 and a hydraulic retention time of 3.6 days. However, by supplementing urea and trace elements a stable operation even at an organic loading rate of 9.6 g COD L −1  d −1 and a hydraulic retention time of 2.5 days was possible, resulting in 79% higher methane production rate with a stable specific methane production of 239 mL g COD −1 .